2022
DOI: 10.1155/2022/8446857
|View full text |Cite
|
Sign up to set email alerts
|

HSPA8 Is a New Biomarker of Triple Negative Breast Cancer Related to Prognosis and Immune Infiltration

Abstract: Objective. Triple negative breast cancer (TNBC) is a kind of cancer that endangers the lives of women all over the world in the 21st century. Heat shock protein member 8 (HSPA8) is the chaperone gene of the heat shock protein family. It is involved in many cellular functions. For example, it promotes the circulation between ATP and ADP, participates in protein folding, and can change the vitality of the cell and inhibit its growth. However, the abnormal expression of HSPA8 gene in TNBC and its diagnostic and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 75 publications
3
9
0
Order By: Relevance
“…Our data showed that HSPA8 increased the IC 50 values and mitophagy, and inhibited ROS production and cell death. Consistent with previous studies [49,50], our findings also suggest that HSPA8 has oncogenic functions.…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed that HSPA8 increased the IC 50 values and mitophagy, and inhibited ROS production and cell death. Consistent with previous studies [49,50], our findings also suggest that HSPA8 has oncogenic functions.…”
Section: Discussionsupporting
confidence: 93%
“…Another study showed that HSPA8 had a higher expression level in high-risk TNBC patients (52), which was in line with our study, manifesting that its abnormal expression was linked to the inferior prognosis of BC patients. Similarly, GFAP had been recommended as a prognostic marker in distinctive cancers, such as malignant astrocytoma (53).…”
Section: Discussionsupporting
confidence: 92%
“…The high levels of carbonylation induced by the HFHS in the kidney also affected chaperon proteins (Pdia3 and Hspa8). These enzymes are responsible for inhibiting misfolded protein aggregation and disulfide bridge formation through the reduction and isomerization of incorrect disulfide bonds to maintain the new synthesized protein native structure [ 88 , 89 ]. Thus, losses of their activity due to carbonylation would contribute to oxidative-induced kidney disease.…”
Section: Resultsmentioning
confidence: 99%